2018
DOI: 10.19184/ams.v4i1.6857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soyflour (Glycine max L.) Hepatoprotector Activity on Liver MDA Level in Male Wistar Rat Induced by Diazinon

Abstract: Diazinon is metabolized in liver becomes diazoxon, an active metabolite form that can cause free radical raisingthat leads to lipid peroxidation. The result of lipid peroxidation is MDA. Soyflour has higher isoflavones than theother processed food of Glycine max L.This isoflavones donate its electron and hydrogen atom in lipidperoxidation so it can block the lipid peroxidation. The aim of this experiment is to investigate the effect of soyflour on MDA hepar level increase of male wistar rat induced by diazinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…for 7 days could significantly increase liver MDA level. A previous study revealed that diazinon 40 mg/kg b.w administered to rats for 5 days significantly increased liver MDA level (Himah, Wisudanti, & Fatmawati, 2018). Another study reported that diazinon 50 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 94%
“…for 7 days could significantly increase liver MDA level. A previous study revealed that diazinon 40 mg/kg b.w administered to rats for 5 days significantly increased liver MDA level (Himah, Wisudanti, & Fatmawati, 2018). Another study reported that diazinon 50 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 94%